When Citizenship demands Care: the inclusion of people with autism in the Brazilian labour market - Aydos, Valeria; Fietz, Helena (Disability Studies Quarterly, 2017)
In the late 2000s, a network of agents started to promote the inclusion of people with disabilities into the Brazilian labor market, through an Affirmative Action Law that requires private companies to include from 2 to 5 % of people with disabilities among their employees. In this context, the experiences of people with autism brought to light theoretical and practical discussions on both the autonomy of these people and the 'best ways' of managing their everyday work routines. Perceiving public policies as producers of both subjects and social relations (Shore, 2010; Biehl & Petryna, 2013; Schuch, 2009), we aim to understand their effects in the management practices of different companies and in the citizenship-making processes (Ong, 2003) involving people with autism. Through ethnographic observation of the work environment in private companies, we highlight some 'Western' values implicit both in the public policies and in management technologies which may clash with the "logic of care" (Mol, 2008). By showing how Citizenship demands Care in this context, and how Care always demands a kind of human dependency, we shed light on the complexity of the notion of Care and aim to problematize the concept of Citizenship itself.